Effect of handling, time of use and photoactivation on the contamination of dental composite resins - Dayane Bezerra Rêgo; Pedro Henrique Sette-; Daniel Fernandes Peixoto; Raniel Fernandes Peixoto (Universidade Estadual de Maringá, 2022)
This study evaluated the effect of contamination of composite resins (CRs) handled by undergraduate students during restorative procedures, varying the time (baseline, 30 days and 60 days) and experimental condition (before and after handling, contamination with saliva [positive control] and photoactivation). Eight CR tubes were randomly distributed at the dental clinic and the samples were organized into four groups: CR fragments collected before (GB) and after (GA) the restorative procedure; CR fragments contaminated with saliva (GS) and photoactivated (GP) both collected after the procedure. These 4 groups were evaluated in 3 different times: baseline (after sealing), 30 days and 60 days of use of the CR. Samples that had positive turbidity in Brain Heart Infusion (BHI) broth were sown in BHI and Sabouraud Dextrose (SB) agars for subsequent counting of Colony Forming Units (CFU mL-1). The results showed that the handling was responsible for increasing contamination (p < 0.05) at the baseline (GB [n = 0] and GA [n = 3]), as well as after 30 (GB [n = 1] and GA [n = 6]) and 60 (GB [n = 1] and GA [n = 5]) days of use. Photoactivation was responsible for the reduction for microorganisms in T0 and T60. Additionally, the time use and conservation did not influence the contamination of CRs. Handling was responsible for the increase of contamination of CR, the photoactivation seems to reduce the number of viable microorganisms and the time of use seems not to potentiate the effect of tube contamination.